Educação contextualizada e a convivência com o semi-árido no assentamento Acauã-PB - Farias., Ana Elizabete Moreira de (2009)
This work is linked to the line of research Regional History, of the course of the mastership of Pos-Graduate in History from UFPB, whose the concentration area is History and Historical Culture Has as main objective, apprehend how the proposed sociability with the brazilian Semi-Arid has favored the (re) signification of education and the history teaching in the Municipal Elementary School Lili Queiroga. In this sense, in the second chapter developed a theoretical discussion of historical culture, school culture, representations and appropriations. Then we question the notion of sociability with the brazilian Semi-Arid from the understanding of what is brazilian Northeast, for to show the transformation the social and cultural in the educational of the Brazilian Semi-Arid context. Continuing, in the third chapter also analyzed legislation, parecer and parameters of the National Education Political, trying comprehend how they possibiliting the debate around the education contextualized. In this chapter also analyzed the didactic book contextualized "Knowing the Brazilian Semi-Arid Region 1 and 2" produced by RESAB and adopted in camp Acauã's elementary school in year 2007. Now in the fourth chapter we understand how the discussion about sociability go possibiliting the (re) construction of new knowledge, principally, referring to historical knowledge. The work's architecture is based in bibliographical source, oral history's methodology and documentary analysis of laws National Education Political.